People Made of Glass: The Collapsing Temporalities of Chronic Conditions - Madsen, Ida Vandsøe (Anthropology of consciousness, 2021)
An increasing number of people worldwide are living with chronic conditions that have an aspect of bodily fragility as part of the condition or as an effect of treatment. In this article, I explore the temporal experience of bodily fragility and the particularities of consciousness states among people with the chronic condition osteogenesis imperfecta (OI) in Denmark. My aim is threefold. First, my goal is to give an insight into life with OI, a rare and rarely studied condition. Second, I shed light on bodily fragility, a theme that lives in the shadows of other analytical foci in anthropology. Third, I will contribute to the anthropological understanding of the connection among body, physical environment, and consciousness. I argue that the lifeworlds of people with OI are haunted by mental and bodily memories and fearful future scenarios, which makes the past and the future collapse into the present.